Frankreich Jahrbuch 2023: Die Gesellschaften Europas und ihre Zukunft. Jubiläumspublikation anlässlich von 75 Jahren dfi | Les sociétés européennes face à leur avenir. Publication à l’occasion des 75 ans du dfi - Deutsch-Französisches Institut; Institut Franco-Allemand (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The dfi has celebrated its 75th anniversary with a representative opinion poll covering Italy, France and Germany: How do Europeans view their future? Can we observe the convergence of views among Europeans or could we even speak of the emergence of a "European society"? Alongside citizens’ perceptions, the contributions analyse the challenges our societies are facing: Contributions in French and German are dedicated to the social consequences of climate change, energy policy and demographic development. Ultimately, the volume poses the question of the consequences the upcoming transformations have for the functioning of our national democracies.With contributions byElena Ambrosetti | Martina Bodo | Mirjam Dageförde | Eileen Keller | Renate Köcher | Hélène Michel | Marc Ringel | Frederike Rübsam | Stefan Seidendorf | Mathilde Viennot